Project Silverlight: Community based and participant-led initiatives to increase civic engagement among older adults - STRAUGHAN, Paulin T. (Institutional Knowledge at Singapore Management University, 2023)
Project Silverlight was a year-long project aimed at redefining social engagement and participation of older adults in the community. In this report, we share our findings from the project and key recommendations to community partners who are looking to adopt a similar model of participant-led programs. Our study found that by engaging student volunteers as a key partner in this initiative, participants showed a significant improvement in their perceptions of youth, and that participants derived a great sense of satisfaction from being involved in the curation of their activities.